DETERMINAN PENYERAPAN TENAGA KERJA DI KOTA MALANG SEBELUM DAN SAAT PANDEMI COVID-19 - Khairi, Irsyad; Shasta Pratomo, Devanto (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
One of the labor problems in Malang City is that the available jobs cannot absorb the rapidly growing labor force, causing high unemployment. The purpose of this study is to determine the effect of minimum wage, GRDP, inflation, education and COVID-19 dummy variables on labor deployment in Malang City. Data analysis uses multiple linear regression methods with the Stata 14 program. The data used are time series from 1993-2022 in Malang City. The results showed that the minimum wage has a positive and significant effect on labor absorption. Education level has a significant and negative effect on labor absorption. GRDP and Inflation have no significant effect on labor absorption. For COVID-19 dummy on employment, it has a negative and insignificant effect during the COVID-19 pandemic